2016
DOI: 10.1155/2016/4765310
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Postpartum Depression: An Overview and Methodological Recommendations for Future Research

Abstract: Emerging research suggests that a relationship exists between breastfeeding and postpartum depression; however, the direction and precise nature of this relationship are not yet clear. The purpose of this paper is to provide an overview of the relationship between breastfeeding and postpartum depression as it has been examined in the empirical literature. Also, the potential mechanisms of action that have been implicated in this relationship are also explored. PubMed and PsycINFO were searched using the keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
112
2
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 102 publications
2
112
2
8
Order By: Relevance
“…Studies on mothers often report a strong association of maternal perinatal depressive symptoms and breastfeeding problems or discontinuation (Dias and Figueiredo, ). This is, however, definitely influenced by individual and societal expectations on breastfeeding (Pope and Mazmanian, ). Both the direction of the aforementioned association and the underlying mechanisms are still under study.…”
Section: Endocrine Changes In Peripartum Depressionmentioning
confidence: 99%
“…Studies on mothers often report a strong association of maternal perinatal depressive symptoms and breastfeeding problems or discontinuation (Dias and Figueiredo, ). This is, however, definitely influenced by individual and societal expectations on breastfeeding (Pope and Mazmanian, ). Both the direction of the aforementioned association and the underlying mechanisms are still under study.…”
Section: Endocrine Changes In Peripartum Depressionmentioning
confidence: 99%
“…(1) Studies show higher rates in Brazil, with prevalence ranging between 7.2% and 39.4% in the cities of Recife and Vitória respectively. (2,3) The main risk factors for developing PPD are the following: inadequate or non-existent family and social support, women's psychiatric history, intense anxiety, previous depressive episodes, infertility, history of gestational loss, and negative feelings about gestation or the baby.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that breastfeeding is a protective factor in the case of postpartum mood swings [18]. Breastfeeding women develop PPD less frequently, suggesting that some hormonal effects associated with lactation may have protective effects on mental health, such as the antidepressant and anxiolytic effects of oxytocin and prolactin.…”
Section: Introductionmentioning
confidence: 99%